2010
DOI: 10.1016/s1734-1140(10)70320-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sildenafil treatment on the development of tolerance to diazepam-induced motor impairment and sedation in mice

Abstract: We studied the effects of sildenafil, a selective inhibitor of PDE5, on the development and the expression of tolerance to diazepam (DZ)-induced motor impairment and sedation in mice. DZ-induced motor incoordination was assessed by the rotarod and chimney tests, and DZ-induced sedation was examined using a photocell apparatus. Sildenafil treatment enhanced the development of tolerance to the motor impairing effects, but not to the sedative effects, of DZ. Sildenafil treatment did not affect the expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…It is worth emphasizing that the doses of drugs modifying l -arginine:NO:cGMP pathway used in the present experiments were chosen on the base of our previous experiments and both acute and chronic administration of NO modulators did not affect the motor performance in mice (Talarek et al 2008; Talarek et al 2010). Therefore, the results of the present study seem not to be associated with motor-impairing effect of these compounds per se.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth emphasizing that the doses of drugs modifying l -arginine:NO:cGMP pathway used in the present experiments were chosen on the base of our previous experiments and both acute and chronic administration of NO modulators did not affect the motor performance in mice (Talarek et al 2008; Talarek et al 2010). Therefore, the results of the present study seem not to be associated with motor-impairing effect of these compounds per se.…”
Section: Discussionmentioning
confidence: 99%
“…FNZ was injected subcutaneously (sc). The doses of drugs modifying l -arginine:NO:cGMP pathway were tested in our previous experiments (Talarek et al 2008; Talarek et al 2010), and those which did not affect the motor performance in mice were used in the present studies. All the substances were administered in a volume of 10 ml/kg body weight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The QUAN-0808 had positive effects in both electrical and chemical tests. These animal models are usually considered suitable for identifying anticonvulsant 1,9 activity againsta variety of seizures. The chemical models of seizure, such as PTZinduced seizures, represent models of'myoclonic seizure' that produce clonic and tonic seizures.…”
Section: Anticonvulsant Activitymentioning
confidence: 99%
“…In contrast, low NO concentrations may affect GABAergic transmission as an inhibitory effect. [31] A decrease in NO amounts is followed by a corresponding decrease in the GABA levels via an increase in the GABA transaminase activity. [32] Naziroglu et al [21] showed no differences in the NO levels in the brain cortex of rats when seizures were induced with PTZ.…”
Section: Mda Determinationmentioning
confidence: 99%